Long-term Late Cretaceous oxygen- and carbon-isotope trends and planktonic foraminiferal turnover: A new record from the southern midlatitudes - FALZONI, FRANCESCA; M.R. Petrizzo; L. J. Clarke; K. G. MacLeod; H. C. Jenkyns (Geological Society of America Bulletin, 2016)
The similar to 35-m.y.-long Late Cretaceous greenhouse climate has been the subject of a number of studies, with emphasis on the Cenomanian-Turonian and late Campanian- Maastrichtian intervals. By contrast, far less information is available for the Turonian-early Campanian interval, even though it encompasses the transition out of the extreme warmth of the Cenomanian-Turonian greenhouse climate optimum and includes an similar to 3-m.y.-long mid-Coniacian-mid- Santonian interval when planktonic foraminifera underwent a large-scale, but poorly understood, turnover. This study presents similar to 1350 delta O-18 and delta C-13 values of well-preserved benthic and planktonic foraminifera and of the <63 mu m size fraction from the Exmouth Plateau off Australia (eastern Indian Ocean). These data provide: (1) the most continuous, highly resolved, and stratigraphically well-constrained record of longterm trends in Late Cretaceous oxygen-and carbon-isotope ratios from the southern midlatitudes, and (2) new information on the paleoecological preferences of planktonic foraminiferal taxa. The results indicate persistent warmth from the early Turonian until the mid-Santonian, cooling from the mid-Santonian through the mid-Campanian, and short-term climatic variability during the late Campanian-Maastrichtian. Moreover, our results suggest the cause of Coniacian- Santonian turnover among planktonic forami-nifera may have been the diversification of a temperature- and/or salinity-tolerant genus (Marginotruncana), and the cause of the Santonian-early Campanian extinction of Dicarinella and Marginotruncana may have been surface-ocean cooling and competition with globotruncanids.